2018
DOI: 10.37358/rc.18.2.6138
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Scaffold and Lipoaspirate Fluid-derived Stem Cells for the Treatment of Cartilage Defects in a Rabbit Model

Abstract: The purpose of the present study was to assess and compare the chondroregenerative properties of PLA (processed lipoaspirate) and LAF (lipoaspirate fluid) cells, in a preclinical rabbit model of knee cartilage defect. The defects were repaired by a collagen I/III scaffold and added LAF-cells, PLA-cells or no cells, upon the study group. The results showed that collagen scaffolds seeded with LAF-derived stem cells appear to have slightly better activity and outcomes when compared to PLA-cells, in terms of carti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Starting with the first collection and isolation of fat cells performed on mice by Rodbell [17], the method was applied thereafter to other animal models, being later modified for use in human models. [18] Benea et al (2018) found on a rabitt model that collagen scaffolds seeded with adipose stem cells derived from lipoaspirate fluid could be a valuable option in cartilage regeneration [19]. Hurmuz et al (2016) suggested that adipose stem cells derived from the human infrapatellar fat pad and isolated by a non-enzymatic method, have similar morphological and phenotypical characteristics with mesenchymal stem cells [20].…”
Section: Abstract: Adipose Tissue Sheep Stem Cells Detomidine Atimentioning
confidence: 99%
“…Starting with the first collection and isolation of fat cells performed on mice by Rodbell [17], the method was applied thereafter to other animal models, being later modified for use in human models. [18] Benea et al (2018) found on a rabitt model that collagen scaffolds seeded with adipose stem cells derived from lipoaspirate fluid could be a valuable option in cartilage regeneration [19]. Hurmuz et al (2016) suggested that adipose stem cells derived from the human infrapatellar fat pad and isolated by a non-enzymatic method, have similar morphological and phenotypical characteristics with mesenchymal stem cells [20].…”
Section: Abstract: Adipose Tissue Sheep Stem Cells Detomidine Atimentioning
confidence: 99%
“…In clinical practice, many surgical interventions need the support given by the synthetic biomaterials. Also, the various aspects related to the interface between synthetic biomaterials and human tissue appear to be interesting not just for neurosurgery [1,2], but also for many clinical specializations like orthopedics [3][4][5][6][7], dentistry [8][9][10], abdominal surgery [11][12][13][14], gynecology [15][16][17][18], cardiovascular surger y [19,20], and ophthalmology [21].…”
mentioning
confidence: 99%
“…The relevance of the adhesion phenomena is important for various clinical specializations like cardiovascular surgery [1], orthopedics [2][3][4][5], dentistry [6][7][8][9], neurosurgery [10,11], abdominal surgery [12][13][14][15], gynecology [16,17], and ophthalmology [18].…”
mentioning
confidence: 99%